Developing trust in face-to-face interaction of knowledge-intensive business services (KIBS) - Growe, Anna (Regional studies, 2019)
The objective of this paper is to understand the reasons for creating temporary spatial proximity in work processes of knowledge-intensive business services. Obligations to create temporary special proximity are linked to developing processes of interpersonal trust. Based on qualitative interviews, focusing and showing appreciation are identified as drivers to create temporary spatial proximity as ‘valuable moments’ throughout project work. Undivided attention in a special and, therefore, valuable moment is created through insulation (outward effect) and bonding (inward effect), which are to be understood as two sides of the same coin and as supporting the development of cognitive trust and affective trust.
Published online: 01 Jun 2018
Gesehen am 10.05.2019
Keywords: Aufsatz in Zeitschrift